(Un)desirable approaches in therapy with Swedish individuals practicing BDSM: client's perspectives and recommendations for affirmative clinical practices. Issue 3 (3rd July 2022) - Lantto, Reid; Lundberg, Tove
ABSTRACT: This transformative study aimed to explore how people who practice BDSM (bondage, discipline, dominance, submission, sadism, masochism) experience therapy; specifically, what sort of therapist responses and qualities they described as problematic and desirable in relation to addressing BDSM in therapy. Semi-structured interviews were conducted with 27 Swedish BDSM practitioners with experiences of psychotherapy. The interviews were analysed using inductive thematic analysis. Three themes were identified: 'A professional stance', relating to how therapists handled their professional roles when BDSM was addressed, 'Therapists' approaches towards BDSM', regarding therapists' opinions and attitudes towards BDSM, and 'Conversations about BDSM', regarding how therapists handled conversation about the topic. Participants reported negative experiences where therapists expressed prejudice, judgment or pathologizing attitudes, failed to contain their own emotions, questioned their clients about BDSM, used their clients to inform themselves about BDSM, avoided or focused excessively on the topic. Positive experiences were characterised by non-judgement, asking client-centred questions, and stimulating a collaborative exploration of matters relevant to the client. BDSM practitioners' experiences of therapy were related to those documented in the literature on other minoritized identities. This study contributes to the growing literature on kink-aware therapy, which makes psychotherapy more affirmative, accessible, and rewarding to BDSM practitioners.